Echinocandins and Continuous Renal Replacement Therapies: The Role of Adsorption - T m Tomasa Irriguible (Archives of Clinical Nephrology - Peertechz Publications, 2018)
The following reviews [1,2], about continuous renal replacement therapies (CRRT) and echinocandins conclude that the membranes do not significantly adsorb these antifungals.